Pengaruh Brand Activation Terhadap Brand Image Whitelab: Survei pada Pengunjung Unveil the New Whitelab - Lailynisa Fadilla Iswadi; Jamiati KN; Daniel Handoko (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Brand Activation is one of the important things for a brand. Brand Activation is a strategy that companies use by providing real experiences for consumers. So the purpose of this study is to determine whether Brand Activation has an influence on Brand Image. The theory used in this research is the theory of Brand Activation through the Experiential Marketing approach which includes, sense, feel, think, act, and relate experience. While the Brand Image theory used includes brand strength, uniqueness, and excellence. This research uses quantitative methodology with survey method. The population used in this study were visitors to the "Unveil the New Whitelab" event who had commented on @whitelab_id's twitter post on November 7, 2022. The data collection technique was carried out by distributing questionnaires to 97 respondents through random sampling technique. The results of this study indicate that Brand Activation has a significant influence of 80.1% on Whitelab's Brand Image.